Academic development in the mainstream: A case study in an undergraduate engineering programme in South Africa - Heydenrych, Hilton; Case, Jennifer M (South African Journal of Higher Education, 2016)
A recent CHE report has highlighted the poor graduation throughputs in South African undergraduate programmes. Academic development constitutes the current university response to these challenges and to date much work has focused on the establishment of foundation programmes. The present case study – centred on the chemical engineering programme at the University of Cape Town - offers an analysis of the possibilities for academic development in the mainstream programme. Quantitative longitudinal analyses of cohort graduate throughput show significant improvements over two decades, both in aggregate and in demographic breakdown. A survey of academic staff in the programme pointed to the significant impact of the establishment, in the early 1990s, of a post focusing on academic development. These findings also gave evidence of a departmental culture centred on critical debate and innovation in the undergraduate programme.